2019
DOI: 10.2147/ott.s230597
|View full text |Cite
|
Sign up to set email alerts
|

<p>JAZF1 Suppresses Papillary Thyroid Carcinoma Cell Proliferation and Facilitates Apoptosis via Regulating TAK1/NF-κB Pathways</p>

Abstract: PurposeJuxtaposed with another zinc finger gene 1 (JAZF1) is involved in gluconeogenesis, insulin sensitivity, cell differentiation, lipid metabolism and inflammation, but its role in carcinoma remains inexplicit.Patients and methodsWe explored the JAZF1 expression in human papillary thyroid cancer (PTC) tissues, adjacent normal thyroid tissues and nodular goitre tissues, as well as Ki67 expression in PTC tissues, using immunohistochemistry staining. Western blotting and RT-qPCR were performed to explore the J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…We showed that JAZF1 was down-regulated in papillary thyroid cancer tissues more than adjacent nonneoplastic tissues, which was similar to results of Huang et al, (2019), whose report was the first in exploring tumor suppressor role of JAZF1 in papillary thyroid carcinoma using immunohistochemistry and they stated that expression of JAZF1 in papillary thyroid carcinoma was decreased in comparison with adjacent thyroid tissues or with nodular goiter. Huang et al, (2019), showed that JAZF1 expression is inversely associated with Ki67 labelling index in cancer cells denoting that JAZF1 made its tumor suppressor function by inhibition of cell proliferation and cell cycle arrest. Yuasa et al, (2015) found different results, showed that increased JAZF1 expression increased cell proliferation and leads to the progression of the cell cycle, which stimulated oncogenesis in muscle.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We showed that JAZF1 was down-regulated in papillary thyroid cancer tissues more than adjacent nonneoplastic tissues, which was similar to results of Huang et al, (2019), whose report was the first in exploring tumor suppressor role of JAZF1 in papillary thyroid carcinoma using immunohistochemistry and they stated that expression of JAZF1 in papillary thyroid carcinoma was decreased in comparison with adjacent thyroid tissues or with nodular goiter. Huang et al, (2019), showed that JAZF1 expression is inversely associated with Ki67 labelling index in cancer cells denoting that JAZF1 made its tumor suppressor function by inhibition of cell proliferation and cell cycle arrest. Yuasa et al, (2015) found different results, showed that increased JAZF1 expression increased cell proliferation and leads to the progression of the cell cycle, which stimulated oncogenesis in muscle.…”
Section: Discussionsupporting
confidence: 87%
“…Thyroid cancer is considered the most prevalent endocrine system cancers that continued rising worldwide in the past decades (Xiao et al, 2019). Papillary carcinoma of the thyroid formed about 74-80% of all thyroid malignancies (Huang et al, 2019). Papillary thyroid cancer has a favourable patients outcome and better patients survival, but it was found that some patients might have more aggressive phenotypes with lack of response to the currently used therapies with high patients morbidity and mortality (Fu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ZBTB10 was regarded to regulate specificity proteins (Sp) by reactive oxygen species (ROS)- microRNA27a 25 . Chen et al proposed that JAZF1 suppresses proliferation and induces apoptosis via TAK1/NF-κB pathways 26 . DCBLD2 over-expression has been implicated in causing tumorigenesis, invasion and metastasis in colorectal cancer expression 27 .…”
Section: Discussionmentioning
confidence: 99%
“…An increase in proliferative capacity when Jazf1 is overexpressed has been reported in several studies, such as in prostate cancer cells, cardiac microvascular endothelial cells, C2C12 cells, and mouse airway epithelial cells [19,30–32]. It has also been reported that Jazf1 inhibits proliferation in cancer cells but not in normal cells [33]. In a study of cardiac microvascular cells, Jazf1 promoted proliferation and angiogenesis via the Akt signaling pathway [30].…”
Section: Discussionmentioning
confidence: 98%